Underpricing in Indonesia: A Systematic Literature Review - M. Reza Oktananda; Evi Gantyowati (Universitas Hayam Wuruk Perbanas, 2024)
This study employs the charting field method to empirically examine the evolution of underpricing research in Indonesia over the past decade (2014-2023). The research is categorized into four main areas: the development of underpricing studies in Indonesia, theoretical mapping, measurement mapping of underpricing, and causal relationship mapping. The findings reveal that underpricing research in Indonesia has advanced over the last ten years, albeit with fluctuations in the number of publications each year. The three most commonly applied theories in this field are signaling theory, information asymmetry theory, and agency theory. Initial return is the most frequently used measure of underpricing, accounting for 79% of the studies. Additionally, the causal relationship mapping highlights that many variables produce inconsistent results, indicating a research gap that future scholars can address. This study lays the groundwork for further exploration of the variables that influence underpricing, particularly by investigating underwriter reputation as a moderating factor. The research has practical implications for various stakeholders: Initial Public Offering (IPO) companies can use the findings to design more effective strategies, investors can rely on them to guide their investment decisions, and regulators can leverage the insights to develop policies that enhance transparency in the IPO process.